Substituição parcial do milho pela palma forrageira em dietas para cabras em lactação - Goveia, Julianne Santiago Silva (2012)
The objective of this trial was to evaluate the effect of the partial replacement of corn by forage cactus (Nopalea cochenillifera- Salm Dyck) in diets of lactating goats on the nutrient intake, production and milk composition and ingestive behavior. Five crossbreed Saanen x Pardo Alpina, with body weight 47 ± 3.3 kg, in second lactation order and up to 60 days of lactation. The design was a 5x5 Latin square and treatments as following: 20, 25, 30, 35 and 40% replacement of corn by forage cactus associated with the gliricidia hay (Gliricídia sepium (Jacq) Walp). Treatments did not affect (P> 0,05) dry matter intake, crude protein, neutral detergent fiber, acid detergent fiber and total digestible nutrients by increasing the levels of forage cactus in the diet presenting means of 1,64; 0,26; 0,82; 0,54 e 1,17 kg/d, respectively. In the same way, there was no influence on the daily milk production and levels of fat, protein, lactose and total solids of milk and averaged 1,18 kg/d; 3,74; 3,34; 5,06 and 13,56%, respectively. The 3,5% fat corrected milk (LCG) presented a quadratic performance (P <0,05). There was not effect (P> 0.05) observed on the time spent in feeding, rumination, idle, total chewing time, feeding and rumination efficiency of dry matter. The treatment with 35% cactus showed lower impairment of income on food (31%). The partial replacement of corn by forage cactus in diets for dairy goats can be performed, because it does not affect the evaluated characteristics, thus the inclusion of 35% forage cactus is recommended because it has lower feed cost.